Penerapan Teknologi Energi Hybrid: Turbin Mikrohidro dan Panel Surya untuk Menambah Produksi Energi Listrik di Dusun Batu Saeng, Tanggamus, Lampung - Madi Madi; Putty Yunesti; Mugi Praseptiawan; Risfihan Rafi; Alfajar Puja Kusuma (Universitas Mathla'ul Anwar Banten, 2022)
APPLICATION OF HYBRID ENERGY TECHNOLOGY: MİCRO-HYDRO TURBİNE AND SOLAR PANELS TO INCREASE ELECTRİCAL ENERGY PRODUCTİON İN DUSUN BATU SAENG, TANGGAMUS, LAMPUNG. Dusun Batu Saeng, Tanggamus, Lampung is one of the areas that utilize the potential of the surrounding natural resources. One of the potentials used is river water which is used as a Micro Hydro Power Plant (PLTMH). However, the source of electrical energy that has been used for 10 years does not appear to be optimal in its utilization. This is because many components are damaged and unfit for use which has reduced their performance. The production of electrical energy from PLTMH is 8 kW which is distributed to 20 houses, this amount will be reduced during the dry season to 6-7 kW. Based on that, it is necessary to replace components such as turbines and generators with a capacity of 10 kW. In addition, during a prolonged dry season, it can also be utilized by installing a 1 kW photovoltaic as a Solar Power Plant (PLTS). Thus, by utilizing water and solar sources, more optimal electricity production can be produced through hybrid energy from PLTMH and PLTS in Dusun Batu Saeng, Lampung. The implementation stages include literature study, site survey, group discussion forum, design and planning, design and preparation, manufacture of PLTMH and PLTS, installation of PLTMH and PLTS, monitoring and evaluation, and final report. The result of this program is an increase in electricity production from 8 kW to 11 kW of hybrid energy from PLTMH and PLTS. It is hoped that in the future this program can be applied to other areas so that they become energy-independent communities.